(untitled) (Nepalese Journal of Development and Rural Studies, 2017)
Agriculture sector is the single largest employer in the world. Even in Nepal, agriculture sector provides net employment to 60 percent people. In this contexts, this study highlighted importance of technological intervention in agriculture development. However, focus was given to assess socio-economic situations of the farmers and impact of modern technological interventions. In so doing, the survey was conducted in Lele Village of Godavari Municipality. The respondents were randomly selected 152 sample households using modern/traditional agriculture technologies. The necessary primary data collected through households’ survey questionnaires, observation and informal communications whereas secondary data generated from published/unpublished books, journals, inter/national reports and local level profiles. The study found that modern technological intervention has been fostering commercial farming activities in Lele village and increased family income, creating self-employment and generating rural economy in particular and supporting to the rural development process in general. Further, local development stakeholders need to provide technical/financial supports to the farmers for mounting intervention of modern agriculture technology in Lele village. The finding of the study has possibility to replicate in similar situation throughout the country. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page: 86-97